# General term

• Mar 10th 2010, 10:51 PM
VonNemo19
General term
I'm having trouble finding the coefficients for the maclaurin series for $\displaystyle f(x)=\sqrt{1-x}$. i have

$\displaystyle \frac{\Pi_{k=2}^n(2k-3)}{2^nn!}$. Is this right?
• Mar 10th 2010, 11:21 PM
simplependulum
By differentiation ,

$\displaystyle f(x) = \sqrt{1-x} = (1-x)^{ \frac{1}{2} }$

$\displaystyle f'(x) = -\frac{1}{2} \cdot (1-x)^{- \frac{1}{2} }$

$\displaystyle f''(x) = - \frac{1}{2} \cdot \frac{1}{2} \cdot (1-x)^{- \frac{3}{2} }$

$\displaystyle f'''(x) = - \frac{1}{2} \cdot \frac{1}{2} \cdot \frac{3}{2} \cdot (1-x)^{- \frac{5}{2} }$

Observation is a good tool to conclude that

$\displaystyle f^{(n)}(x) = - \frac{1}{2} \cdot \frac{1 \cdot 3 ... \cdot (2n-3) }{ 2^{n-1} } \cdot (1-x)^{- \frac{2n-1}{2} }$ ( Isolate the first $\displaystyle \frac{1}{2}$ ) $\displaystyle n \geq 2$

Therefore ,

$\displaystyle f^{(n}(0) = - \frac{1}{2} \cdot \frac{1 \cdot 3 ... \cdot (2n-3) }{ 2^{n-1} }$

But if we " fill up " the spaces between the odd numbers ,

$\displaystyle 1 \cdot 3 \cdot 5 \cdot ... \cdot (2n-3)$

$\displaystyle = 1 \cdot 2 \cdot 3 \cdot 4 ... \cdot (2n-3) \cdot (2n-2)$$\displaystyle \cdot \frac{1}{2 \cdot 4 \cdot ... \cdot (2n-2)}$

$\displaystyle = \frac{ (2n-2)!}{ 2^{n-1} \cdot (n-1)!}$

we will find that

$\displaystyle f^{(n)}(0)$ is also equal to :

$\displaystyle - \frac{ (2n-2)! }{ 2^{2n-1} (n-1)! }$

When accompanying with $\displaystyle \frac{1}{n!}$ to form the coefficient for the Maclaurin series , we can obtain an elegant expression .

$\displaystyle - \frac{ (2n-2)! }{ 2^{2n-1} (n-1)! n! }$

$\displaystyle = - \frac{ (2n-2)! }{ 2^{2n-1} (n-1)! n! } \cdot \frac{ (2n-1)(2n) }{ n } \cdot \frac{n}{2n(2n-1)}$

$\displaystyle = - \frac{ \binom{2n}{n} }{ 2^{2n} (2n-1) }$

$\displaystyle = - \frac{1}{4^n} \frac{ \binom{2n}{n} }{ 2n-1}$